Real‐world evidence on clinical outcomes of people with type 1 diabetes using open‐source and commercial automated insulin dosing systems: A systematic review. Issue 5 (24th November 2021) - Knoll, Christine; Peacock, Sofia; Wäldchen, Mandy; Cooper, Drew; Aulakh, Simran Kaur; Raile, Klemens; Hussain, Sufyan; Braune, Katarina
Abstract: Aims: Several commercial and open‐source automated insulin dosing (AID) systems have recently been developed and are now used by an increasing number of people with diabetes (PwD). This systematic review explored the current status of real‐world evidence on the latest available AID systems in helping to understand their safety and effectiveness. Methods: A systematic review of real‐world studies on the effect of commercial and open‐source AID system use on clinical outcomes was conducted employing a devised protocol (PROSPERO ID 257354). Results: Of 441 initially identified studies, 21 published 2018–2021 were included: 12 for Medtronic 670G; one for Tandem Control‐IQ; one for Diabeloop DBLG1; two for AndroidAPS; one for OpenAPS; one for Loop; three comparing various types of AID systems. These studies found that several types of AID systems improve Time‐in‐Range and haemoglobin A1c (HbA1c ) with minimal concerns around severe hypoglycaemia. These improvements were observed in open‐source and commercially developed AID systems alike. Conclusions: Commercially developed and open‐source AID systems represent effective and safe treatment options for PwD of several age groups and genders. Alongside evidence from randomized clinical trials, real‐world studies on AID systems and their effects on glycaemic outcomes are a helpful method for evaluating their safety and effectiveness.